Atomic configurations of planar defects in μ phase in Ni-based superalloys. (1st March 2021) - Cheng, Yongxin; Wang, Guanglei; Liu, Jide; He, Lianlong
Abstract: μ topologically close-packed phase commonly forms in superalloys and its intrinsic deformation is critical for their performance. Atomic configurations of planar defects in μ phase have been investigated by aberration-corrected scanning transmission electron microscopy and geometrical structure analysis. It is found that the basal slip in μ phase is accomplished by synchroshear inside Laves triple-layers, whereas shear deformations on non-basal planes are associated with long-range diffusions or local atomic rearrangements. Distinct from that on (1 1 ¯ 02) pyramidal planes, displacement vectors of planar faults on ( 1 ¯ 101) pyramidal planes deviate from the slip plane, leading to the contraction or dilation faulted regions. Graphical abstract: Image, graphical abstract